Proceedings of the 13th International Conference on Software Engineering - ICSE '08 2008
DOI: 10.1145/1368088.1368166
|View full text |Cite
|
Sign up to set email alerts
|

Time-bounded adaptation for automotive system software

Abstract: Software is increasingly deployed in vehicles as demand for new functionality increases and cheaper and more powerful hardware becomes available. Likewise, emerging wireless communication protocols allow the integration of new software into vehicles, thereby enabling time-bounded adaptive response to changes that occur in mobile environments. Examples of time-bounded adaptation include adaptive cruise control and the dynamic integration of location-aware services within fixed time bounds.This paper provides th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In prior work [10] we identified the need for dynamic software adaptation in next-generation embedded systems, such as automotive systems. This paper presented a constraintbased scheduling algorithm that maximises the available adaptation actions that can be execute on modules within given time bounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In prior work [10] we identified the need for dynamic software adaptation in next-generation embedded systems, such as automotive systems. This paper presented a constraintbased scheduling algorithm that maximises the available adaptation actions that can be execute on modules within given time bounds.…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation embedded systems in domains such as automotive, avionics or robotics need to adapt swiftly to changing environmental conditions [12]. In prior work [10] we have shown that these systems require varying levels of support for dynamic adaptation, ranging from limited support for fault tolerance in safety-critical systems, to dynamic adaptation of resource Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page. To copy otherwise, to republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ramirez et al [24] propose the use of Genetic Algorithm to generate control strategies that account for actuation delay of the different control actions; Fritsch et al [10], [11] propose a time-bounded scheduling algorithm for control actions in the automotive domain; and Gambi et al [12] propose a novel technique based on model predictive control that accounts for delayed effects of scaling actions in the cloud. Consistently, all of these researchers acknowledge the importance of actuation delays, but assume that their values are known and constant.…”
Section: A Motivationmentioning
confidence: 99%
“…For example, an intelligent transportation system [4], as shown in Figure 1, that coordinates its operations with many intersections in a city may have a UML model of the system's conceptual implementation (e.g., classes, sequence, and use-case diagrams), a formal model to verify functional properties (e.g., deadlock and state reachability), and a system execution model to validate nonfunctional properties (e.g., worst-case system execution time). Moreover, different portions of the system may be developed by different groups dispersed throughout a region, which implies differentpossibly conflicting-underlying concerns and assumptions of the system under development.…”
Section: Figure 1: Intelligent Transportation Systemmentioning
confidence: 99%